(untitled) (Research, Society and Development, 2022)
The objective of this research was to carry out a survey in the literature on the therapeutic actions of the cashew exudate (gum). A search was carried out in the Scielo, Bireme and PubMed databases, during the months of August to September 2022. 208 articles were found, of which 114 were analyzed and 24 were included in this research. Among them, there is the antimicrobial action (cited by 7 articles), anti-inflammatory (cited by 6 articles), gastroprotective and antitumor (cited by 4 articles), and some actions in lesser applications and concomitant in studies such as antinociceptive, antidiarrheal, healing, immunomodulatory and cryopreserving. It is concluded that the bibliographic survey is of fundamental importance for the expansion of scientific knowledge about the pharmacotherapeutic use of Goma do Cajueiro (CG).